IMPLEMENTASI HUKUM ISLAM DI INDONESIA PERSPEKTIF SOSIOLOGIS - Andi Muhammad Akmal (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2019)
Socio-cultural change in society demands a change in law. This is where sociological considerations are urgent in the enforcement of Islamic law in Indonesia. Islamic law is doctrinal and normative, but on the other hand it accepts changes and in its application there is always a door to ijtihad which gives an opportunity to adjust to its empirical reality. There are many fiqh rules that intersect with these arguments. From the various approaches to the rule, it can be understood that Islamic teachings are always in accordance with the principles of development and the dynamics of society. The implementation of the enforcement of Islamic law in Indonesia with sociological considerations can be seen from the ulama's fatwa, especially the fatwas of the Indonesian Ulema Council (MUI).